Multiple Classifier Constructions in Chinese: Semantic Representations and Interpretation Mechanism - Yongzhong Yang (Acta Linguistica Asiatica)
After critically reviewing previous analyses, this paper proposes an alternative explanation, arguing that the basic structure of multiple classifier constructions (MCC) in Chinese is either number phrase + determiner phrase or vice versa, together forming a whole constituent. MCCs require a definite nominal phrase that can be bound by an existential quantificational operator. A nominal phrase that denotes specificity cannot be bound this way and thus cannot act as a distributor. The demonstrative acts as a quantificational or distributive operator that matches, individualizes, and marks the following constituent as singular or plural, representing both atoms and sets. This semantic property ensures that classification or distribution matching corresponds to the individual elements within the set referred to by the distributive share. MCCs thus allow two semantic interpretations.